2000
DOI: 10.1053/rmed.2000.0871
|View full text |Cite
|
Sign up to set email alerts
|

The availability of smoking cessation advice from health professionals — a census from one East London District

Abstract: A survey of 382 hospital inpatients and a survey of 500 adults attending a GP open access chest X-ray service showed that 18% and 25% respectively were current smokers. Sixty per cent of the inpatient smokers and three quarters of the community smokers expressed a wish to stop smoking, and 44% of the inpatient smokers and 62% of the community smokers reported having received advice from their primary care physician to stop smoking. However, when the community smokers were asked about more specific advice they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It is interesting to note that Dutch COPD nurses show a comparable pattern of addressing the smoking behaviour of patients [36]. A study in which patients were asked to report on the smoking cessation advice provided by their primary care physician found considerably less advisory behaviour by physicians than reported by the pulmonologists in our study [37]. This might be related to the nature of the discipline, as it seems plausible that pulmonologists would pay more attention to the smoking behaviour of COPD patients because they are suffering from a smoking-related disease.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…It is interesting to note that Dutch COPD nurses show a comparable pattern of addressing the smoking behaviour of patients [36]. A study in which patients were asked to report on the smoking cessation advice provided by their primary care physician found considerably less advisory behaviour by physicians than reported by the pulmonologists in our study [37]. This might be related to the nature of the discipline, as it seems plausible that pulmonologists would pay more attention to the smoking behaviour of COPD patients because they are suffering from a smoking-related disease.…”
Section: Discussionmentioning
confidence: 50%
“…A Cochrane review showed that training health professionals to provide smoking cessation interventions has measurable effects on professional performance and patients' smoking cessation behaviour [49]. As mentioned above and suggested earlier by Kava et al [37], training should emphasize skills in telling patients how to quit smoking and supporting them in doing so, since pulmonologists are already assessing patients' smoking behaviour and advising them to stop smoking.…”
Section: Practice Implicationsmentioning
confidence: 99%
“…[26][27][28][29][30] This suggestion is supported by the continuing low levels of smoking-care provision in countries that have previously released smoking-cessation care guidelines. 18,23,[31][32][33][34][35][36] Best practice strategies to increase provision of smoking care Guidance regarding the most effective strategies to increase smoking care potentially comes from several sources, including evidence from literature reviews, evidence from well designed individual studies and comments from experts in the field. Currently, there is no review that specifically examines the effectiveness of strategies designed to increase smoking care in hospitals.…”
Section: Barriers To Smoking-care Provisionmentioning
confidence: 99%